منهج الوسطية في تنزيل الحكم الشرعي وتطبيقاته في إقليم كوردستان العراق : دراسة تحليلية تقويمية - أحمد، كوسرت صالح (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The aim of the research is to analyze the issue of the practice of the Islamic ruling control in the Kurdistan Region of Iraq, and evaluate through the method of moderation in the controlling of the shar'i ruling in order to be a contributor to finding a central proposal object with recent reality to solve the problem of lack of control and confusion. In an attempt to be the keystone for the establishment of a juristic in Iraqi Kurdistan in the future. In this research, the researcher relied on the inductive method in reviewing the original sources and the contemporary references in the fundamentals of Islamic jurisprudence and its jurisprudence, and following the views of the fundamentalists and the scholars of the Ummah regarding the downloading of the Islamic ruling, its rules, its standards and stages and how to reconcile jurisprudence. The researcher also took the analytical approach in presenting the control of the Islamic ruling from theory to reality and analyzing the data presented in order to deduce the best possible result regarding the status given to the reduction of the Islamic ruling in the face of the purposes of Shari'a and the interests of the people. In addition, the researcher presented the method of criticism, where the researcher offers ways to the control of the Islamic rule in the region, with the study of models of Fatwas that issued, criticism and evaluation by means of the origins of Islamic jurisprudence and contemporary reality, reinforced by evidence, and discuss objectively. The researcher suggested that the method of moderation in the control of the Islamic rule, and the establishment of jurisprudence in Kurdistan Iraq, and that the importance of the procedure of the advisory opinion in the region is not moderate approach. Also, the organization and control of the process of Islamic advisory opinion is not less important than the establishment of the official organs of the state; therefore, we propose efforts and work by various legitimate means to establish it as soon as possible.